Myrtaceae no Parque Estadual de Vila Velha, Ponta Grossa, Paraná, Brasil - Hessel, Olivia (Universidade Federal de São Carlos, 2018)
Myrtaceae is a family with about 145 genera and approximately 6000 species. Myrteae is the tribe that represents the fleshy fruit species of the family in South America, possessing translucent scores on the leaves, usually visible marginal ridges, flowers with usually white petals, 4-5 free petals, usually many stamens and infertile ovary. The work aimed the taxonomic study of the Myrtaceae species of the State Park of Vila Velha (PEVV), Ponta Grossa, Paraná, with field expeditions were carried out and consultations to the main herbarium collections with representation of the region. Its vegetation is composed of Cerrado and Atlantic Forest. The family is represented in the area by 10 genera and 38 species: Blepharocalyx (1 sp.), Calyptranthes (2 spp.) Campomanesia (3 spp.), Curitiba (1 sp.), Eugenia (9 spp.), Myrceugenia (1 sp.), Myrcia (9 spp.) Myrciaria (4 spp.), Myrrhinium (1 sp.) and Psidium (7 spp.). Morphological descriptions with comments, identification keys and photographic records were made. The study area is represented by monotypic species that have a very restricted distribution, with Myrrhinium atropurpureum occurring only in the Southeast and South and Curitiba prismatica occurring only in the South (Paraná and Santa Catarina).
Myrtaceae in the Vila Velha State Park, Ponta Grossa, Paraná, Brazil
Keywords: Identification keys; flora; southeastern of Paraná; taxonomy; Botânica - Classificação; Botany - Classification; CIENCIAS BIOLOGICAS::BOTANICA::TAXONOMIA VEGETAL